PERFORMANCE ANALYSIS AND EVALUATION OF MASSIVE MIMO SYSTEM - AL-RAWI, Muaayed F.; ABBOUD, Izz K.; AL-AWAD, Nasir A. (Applied Computer Science, 2020)
This article examines the performance of massive MIMO uplink system over Rician fading channel. The performance is estimated regarding spectral efficiency versus number of base station antennas utilizing three plans of linear detection, maximum-ratio-combining (MRC), zero forcing receiver (ZF), and minimum mean-square error receiver (MMSE). The simulation results reveal that the spectral efficiency increments altogether with expanding the quantity of base station antennas. Additionally, the spectral efficiency with MMSE is superior to that with ZF, and the last is superior to that with MRC. Furthermore, the spectral efficiency diminishes with expanding the fading parameter.